kemampuan Pengenalan Huruf Anak Usia 4 Tahun : Studi Kasus Pada “ Soraya “ - Remi Fitriani; Dodi Oktariza; Dedi Efendi (Fakultas Sastra Universitas Ekasakti, 2025)
This study aims to describe the letter recognition skills of 4-year-old children through a case study approach. The focus of the study includes children's ability to recognize letter shapes, name letters, and distinguish letters that have similar shapes and sounds. This study used a qualitative method with a case study design. The subject of the study was a 4-year-old child who was selected purposively. Data collection techniques were carried out through observation, interviews with parents, and documentation of learning activities. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results showed that children's letter recognition skills developed gradually, marked by the ability to name most letters of the alphabet and recognize the first letter of certain words, although still experiencing difficulty in distinguishing some letters that have similar shapes. These findings indicate that environmental stimulation and adult guidance play an important role in supporting the development of letter recognition skills in early childhood. This study is expected to contribute to educators and parents in designing early literacy learning strategies that are appropriate to the child's developmental stage.